2004
DOI: 10.1016/j.biocontrol.2003.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of natural enemies in cotton: role of insect growth regulators in management of Bemisia tabaci

Abstract: Field studies were conducted from 1997 to 1999 to contrast the effects of two insect growth regulators (IGRs) and conventional insecticides on natural enemy conservation in cotton within the context of alternative management strategies for Bemisia tabaci (Gennadius). Compared with an untreated control, insecticide regimes based on the initial use of the IGR buprofezin or pyriproxyfen reduced densities of eight predator taxa out of 20 examined in at least one year, including common species such as Geocoris punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 46 publications
(66 reference statements)
3
74
0
3
Order By: Relevance
“…Field studies of insecticide effects on natural enemies integrate many factors, including direct toxicological effects and reduction in prey availability (Naranjo et al 2004). Our results supported the previous hypothesis (Beattie et al 1995b) that Petroleum spray oils can be selective in protecting the natural enemy components.…”
Section: Discussionsupporting
confidence: 88%
“…Field studies of insecticide effects on natural enemies integrate many factors, including direct toxicological effects and reduction in prey availability (Naranjo et al 2004). Our results supported the previous hypothesis (Beattie et al 1995b) that Petroleum spray oils can be selective in protecting the natural enemy components.…”
Section: Discussionsupporting
confidence: 88%
“…1b). Insect growth regulators (IGRs), which are considered less harmful to nontarget arthropods than broad-spectrum insecticides, are used in Arizona for controlling the sweet potato whitefly (Bemisia tabaci) in cotton (11)(12)(13)(14). Use of IGRs did not differ significantly between transgenic and nonTr cotton ( Table 2, which is published as supporting information on the PNAS web site).…”
mentioning
confidence: 98%
“…Not only are the new products more effective control agents at reduced rates compared to conventional insecticides, their generally narrower activity spectra make possible a more finessed approach to pest management. As the Israeli and Arizona examples have shown with the IGRs buprofezin and pyriproxyfen, treatments have proven less destructive to biological control agents while simultaneously providing better direct control of B. tabaci (Naranjo et al 2004). The thorough research that identified the bio-residual phenomenon for the IGRs has yet to be performed for newer MoAs, but preliminary findings suggest that some also show a high degree of compatibility with beneficial insects.…”
Section: Refine Insecticide Usementioning
confidence: 97%